Fluorescence Microscopy—An Outline of Hardware, Biological Handling, and Fluorophore Considerations - Shane M. Hickey; Ben Ung; Christie Bader; Robert Brooks; Joanna Lazniewska; Ian R. D. Johnson; Alexandra Sorvina; Jessica Logan; Carmela Martini; Courtney R. Moore; Litsa Karageorgos; Martin J. Sweetman; et al. (Cells, 2021)
Fluorescence microscopy has become a critical tool for researchers to understand biological processes at the cellular level. Micrographs from fixed and live-cell imaging procedures feature in a plethora of scientific articles for the field of cell biology, but the complexities of fluorescence microscopy as an imaging tool can sometimes be overlooked or misunderstood. This review seeks to cover the three fundamental considerations when designing fluorescence microscopy experiments: (1) hardware availability; (2) amenability of biological models to fluorescence microscopy; and (3) suitability of imaging agents for intended applications. This review will help equip the reader to make judicious decisions when designing fluorescence microscopy experiments that deliver high-resolution and informative images for cell biology.